Surface deterioration of monolithic CAD/CAM restorative materials after artificial abrasive toothbrushing - Şen, Nazmiye; Tuncelli, Betül; Göller, Gültekin (XMLink, 2018)
The purpose of this in vitro study was to evaluate the effect of abrasive toothbrushing on the surface properties of monolithic computer-assisted design and computer-assisted manufacturing (CAD/CAM) materials stored in food-simulating liquids (FSLs).Fourty-eight disk-shaped test specimens of each material (Paradigm MZ100/PMZ, Lava Ultimate/LU, Vita Enamic/VE, and Vita Mark II/VMII) with a diameter of 10.0 mm and a thickness of 3.0 ± 0.05 mm were prepared. Specimens were divided into 4 subgroups (n=12) and stored in air, distilled water, 0.02 M citric acid, or 75% ethanol/water solution for 7 days at 36.5℃. Then, the specimens were brushed in a multi-station brushing machine under a vertical load of 2.0 N for 3 hours. Surface gloss (GU), roughness (Ra), and hardness (Vickers [VHN]) were measured after storage and brushing simulation. The data sets were statistically analyzed with 2 and 3-way ANOVAs followed by the Tukey's post-hoc comparisons (α=.05).Statistically significant difference was found among the materials concerning the results of surface properties. VMII showed the highest VHN, while PMZ produced the lowest. Storage in FSLs significantly affected the VHN of PMZ and LU. VMII showed the lowest Ra and highest GU irrespective of FSLs and of abrasive toothbrushing. VE, LU, and PMZ produced significant decrease in GU and increase in Ra after toothbrushing.Surface properties of monolithic CAD/CAM restorative materials were differently affected by the storage media and abrasive toothbrushing.
Keywords: Original Article